CHALLENGES AND OPPORTUNITIES OF ONLINE LIBRARY SERVICES IN THE NEW NORMAL: THE WESTERN MINDANAO STATE UNIVERSITY EXPERIENCE - Benhur Abdulaup Asid (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
As higher education institutions strictly follow health protocols due to the COVID-19 pandemic, moving of classes including the closing of libraries is a way of helping the government to mitigate the spread of Coronavirus. To that effect, libraries have also responded to the challenging needs in the educational system. In the Western Mindanao State University library where online services are offered, where the purpose of this study attempted to look into the challenges and opportunities faced by its stakeholders and the extent of satisfaction. The quantitative-qualitative research design employing a descriptive survey method was used. In the selection of respondents, systematic random sampling was also employed, and the five (5) point Likert-type questionnaire checklist was utilized. While a purposive sampling was also employed to library personnel. A total of 384 respondents coming from the students, faculty administrative personnel/staff, and library personnel were utilized. Based on the findings, OLC or the Online Library Cart facilitated by a social media platform was a big help to educators and learners in the academic community. The challenges and opportunities have also brought in the delivery of online services’ operation. The low internet connectivity and lack of personnel competency in the online delivery, among others were considered as challenges. In attaining quality library service, increase in the acquisition of e-resources, upgrading of personnel’s skills as well as strengthening the culture of partnership and collaboration are major factors to create an avenue to improve library services, the online delivery, in particular. The overall mean of 4.74 revealed a high level of satisfaction result from the three groups of respondents, implying that WMSU library online services are very much effective and functioning excellently. It is, therefore, concluded that online services offered by the WMSU Library should be sustained not only to respond to the COVID-19 pandemic but also to support the challenging needs of blended learning education in Western Mindanao.